PENATALAKSANAAN FISIOTERAPI PADA CALCANEUS SPURS SANISTRA DENGAN MODALITAS ULTRASOUND DAN TERAPI LATIHAN - Milla, Meidiana Nurul; Wibisono, Irawan (Jurnal Keperawatan dan Kesehatan, 2025)
Calcaneus spur is an abnormal bone growth on the inferior calcaneus that may cause pain and functional limitations. This study aimed to determine the effectiveness of ultrasound and exercise therapy in a patient with calcaneus spur sinistra through a case study with four treatment sessions. Interventions included ultrasound and exercises such as towel stretch, myofascial release, and calf raises. The results showed decreased tenderness, movement-related pain, and gastrocnemius spasm, along with increased muscle strength, joint range of motion, and functional activity based on the FADI score. In conclusion, ultrasound and exercise therapy are effective in reducing symptoms and improving functional movement in calcaneus spur cases. Keyword: Static Contraction, Active Exercise, Passive Exercise, Resisted Exercise, Hold Relax.